Vems är staden? - Forsemalm, Joakim (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2003)
This article sheds light on the problematic relation between "integration" and the implementation of planning policies. Another more general viewpoint is the complexity of cities. Processes of segregation and territoriality represent a compound and energetic force in contemporary urban cultures. The source material has been collected in Gothenburg. Where, geographically, is the realisation of integration supposed to occur? What is the meaning of "integration" when argued in planning processes that relate to inner-city transformation? Another perspective on urban development opens up the power of image making. The cultural image of "Långgatorna" (well-known streets in western part of the city) is transformed into a landscape of integration policies. Many people are convinced that the streets have an "identity" and that you get a "continental feeling" when moving around. The urban environment along the "Långgatorna" streets has a typical pre-gentrification character with a variety of alternative shops and businesses, premises for music and art etc. and its future is under vigorous discussion in the local media and through different networks. The article suggests that the segregation/integration-problem is an important, still demanding object of cultural analysis.